Gender equality in the position of elementary school principals: still an issue of current interest? - Bobeth-Neumann, Wiebke (Swiss Journal of Educational Research, 2018)
This paper analyzes the unproportional gender ratio in the position of elementary school principals. Using qualitative research the parameter gender and its influence on the career advancement were explored. Furthermore the gendered attribution, covered mechanism of doing gender and a variety of career paths were exposed. The following findings are reported: Male elementary school teachers are being encouraged by the social field to make their way to the principal›s office. In the context of male teachers career advancement is connoted positively. In contrast teacher careers to elementary school principals get a rather negative attribution, when they are focused by female teachers. Besides female teachers seeking to become principals nearly don´t get any encouragement.